The Relative Importance of Phytoplankton Light Absorption and Ecosystem Complexity in an Earth System Model. (17th May 2021) - Asselot, Rémy; Lunkeit, Frank; Holden, Philip B.; Hense, Inga
Abstract: We investigate the relative importance of ecosystem complexity and phytoplankton light absorption for climate studies. While the complexity of Earth System models (ESMs) with respect to marine biota has increased over the past years, the relative importance of biological processes in driving climate‐relevant mechanisms such as the biological carbon pump and phytoplankton light absorption is still unknown. The climate effects of these mechanisms have been studied separately, but not together. To shed light on the role of biologically mediated feedbacks, we performed different model experiments with the EcoGENIE ESM. The model experiments have been conducted with and without phytoplankton light absorption and with two or 12 plankton functional types. For a robust comparison, all simulations are tuned to have the same primary production. Our model experiments show that phytoplankton light absorption changes ocean physics and biogeochemistry. Higher sea surface temperature decreases the solubility of CO2 which in turn increases the atmospheric CO2 concentration, and finally the atmospheric temperature rises by 0.45°C. An increase in ecosystem complexity increases the export production of particulate organic carbon but decreases the amount of dissolved organic matter. These changes in the marine carbon cycling, however, hardly reduces the atmospheric CO2 concentrations and slightly decreases the atmospheric temperature by 0.034°C. Overall we show that phytoplankton light absorption has a higher impact on the carbon cycle and on the climate system than a more detailed representation of the marine biota. Plain Language Summary: Climate models are used to evaluate how climate will continue to change on timescales relevant for human beings. However, they are complex and need to be simplified to run them even on supercomputers. Usually physical processes are very well resolved while biological processes gain less attention. We focus on biological processes and investigate which of them turn out to be particularly important for the climate system so that they should be included in climate models. We are aware that phytoplankton changes the optical properties, redistributing the heat in the ocean. We have also known for a long time that the marine organisms remove carbon from the system by CO2 ‐uptake and downward transport of organically bound carbon by migration or sinking. Yet, the relative importance of these two processes are unknown. Our study suggests that phytoplankton light absorption has a higher impact on the climate system than increasing ecosystem complexity. Phytoplankton light absorption should thus be included by default in models carrying out climate change scenarios. Key Points: We investigate the relative importance of ecosystem complexity and phytoplankton light absorption with the Earth System model (ESM) Eco Grid‐ENabled Integrated ESM (EcoGENIE) Phytoplankton light absorption increases the sea surface temperature (SST) while a higher ecosystem complexity leads to a slightly deeper downward flux of organic matter Our results suggest that phytoplankton light absorption has a higher impact on the climate system than increasing ecosystem complexity